2019
DOI: 10.2147/ott.s215390
|View full text |Cite
|
Sign up to set email alerts
|

<p>Star Circular RNAs In Human Cancer: Progress And Perspectives</p>

Abstract: Circular RNAs (circRNAs) are a recently discovered subclass of non-coding RNAs (ncRNAs) characterized by a covalently closed loop structure created by reverse splicing. Because they do not have a 5ʹ cap structure and a 3ʹ poly A tail, circRNAs have higher stability, abundance and evolutionary conservation than linear RNA between species. These features produce various potential biological functions of circRNAs, such as miRNA sponges, RNA-binding proteins that form RNA protein complexes. In recent years, more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…Circular RNAs (circRNAs), characterized by high stability and conservation, have been increasingly demonstrated to function as the novel promising therapeutic RNA molecules for diverse human diseases, including cancers 27 . Previous studies had shown that several circRNAs correlated with pathogenesis, clinical pathological and prognostic for HCC diagnosis 28, 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNAs (circRNAs), characterized by high stability and conservation, have been increasingly demonstrated to function as the novel promising therapeutic RNA molecules for diverse human diseases, including cancers 27 . Previous studies had shown that several circRNAs correlated with pathogenesis, clinical pathological and prognostic for HCC diagnosis 28, 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Some circRNAs can be detected in peripheral blood and can be used as early diagnostic markers for many cancers, including lung cancer [10]. Then, exploring the potential role of circRNAs in cancer may help to verify therapeutic targets and develop new targeted therapeutic drugs [11,12]. However, there are few reports on their role in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Largely, circRNAs can be organized into ve classes: circRNAs from introns, intergenic circRNAs, exonic circRNAs, exon-intron circRNAs, and antisense circRNAs (7), which are generated from diverse mechanisms including exon skipping, intron pairing and RNA-binding proteins (8). Recently, studies have discovered that circRNAs are intimately related to the incidence and establishment of tumors (7,(9)(10)(11). CircRNAs can perform as competitive endogenous RNAs (ceRNAs) and protect the target mRNA from degradation by sponging microRNA (miRNA) (12).…”
Section: Introductionmentioning
confidence: 99%